If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14-20q=-10-7q-17q
We move all terms to the left:
14-20q-(-10-7q-17q)=0
We add all the numbers together, and all the variables
-20q-(-24q-10)+14=0
We get rid of parentheses
-20q+24q+10+14=0
We add all the numbers together, and all the variables
4q+24=0
We move all terms containing q to the left, all other terms to the right
4q=-24
q=-24/4
q=-6
| 29x+1=3^x | | -2x-38=7(X+1) | | x÷-12+63=66 | | 1x+3=5x+11 | | (n+3)(n-7)= | | 7b+42=133 | | 5x-30-8=22 | | -5.1j-7.81=-2.31+14.7j-19.3j | | 15-3x=5+.5x | | 3x+6=115 | | x+49=46 | | -4(x+5)+6=-14 | | 3(x+1=27 | | 4(2x-3)=6x+12+2 | | -17+2y=17y-13y+9 | | y+1.5=-3.4 | | 4-c=-1/3* | | 32 x−28=46 | | 10x-35=-66 | | 5x+9=2x+7+3x+-15 | | 56-x=18 | | 6g=1+6g | | 4x7+3=5x7-4 | | 11x+2+6x+3=90 | | 3=a-2 | | 18m+50=20m | | 20-9d+5=-19d-15 | | -8+8x=4(5+x) | | 4(x-1)+3x+15=60 | | -8x+17=34 | | 4x+3x-4=2x+31 | | -3(2y+1)=3(1-y)-3y |